Cue-based feeding in the NICU—a pathway to earlier oral feeding of preterm infants - Ofek Shlomai, Noa; Mordechai, Chen; Morag, Iris; Bdolach Abram, Tali; Eventov Friedman, Smadar (Frontiers in Pediatrics, 2024)
Aim To compare volume-driven and cue-based feeding of low birth weight preterm infants, regarding short-term outcomes, including transition to oral feeds, weight gain, and length of stay. Methods This was a retrospective cohort study. Feeding and weight gain outcomes were compared between infants fed by volume-driven and cue-based feeds. The groups were subdivided by birth weight categories. Results The study group included 240 low birth weight preterm infants born before 34 weeks of gestation, 120 infants fed by volume-driven feeding were compared to 120 infants fed by cue-based feeding. The groups were sub-analyzed by birth weight categories: <1,500 g and 1,500–2,500 g. Study groups were comparable regarding baseline characteristics and neonatal morbidities. Infants fed by cue-based feeding were more likely to achieve full oral feeding faster and at an earlier gestational age. Infants with a birth weight <1,500 g were less likely to experience adverse respiratory episodes during cue-based feeding. Although the rate of weight gain was reduced in cue-based feeding in the heavier infant group, discharge weight, breastfeeding rates, and length of stay were comparable between the groups. Conclusions Cue-based feeding results in faster transition to full oral feeding in very low birth weight preterm infants and at an earlier gestational age.